PENGARUH STRUKTUR PASAR TERHADAP PROFITABILITAS INDUSTRI PERBANKAN INDONESIA - , ANNISA PUSPASARI A; , Mudrajad Kuncoro, Prof. Dr., M.Soc.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
There are two competing hypothesis with regard to market structure and performance in industrial organization. First, Structure-Conduct-Performance (SCP) hypothesis which emphasized on market power. Second, Efficient Structure (ES) hypothesis which emphasized on market efficiency. The objective of this study is to analyze which hypothesis from both that reflects Indonesiaâs commercial banking industry. The result of the panel data analysis conducted on a sample of 10 biggest commercial banks over the period from 2008 to 2012 showed to reject both hypothesis. This study finds that Indonesiaâs banking industry doesnât concentrated on the biggest four banks and the profitability of Indonesiaâs banking industry doesnât determined by efficiency behavior.